(untitled) (Historia, 2021)
For those of you who are interested in a spiritual feminist window on life, an infinite number of titles avail themselves in your local bookstore. But before you rush into buying one, you might want to read Eller’s critical monograph first. The Myth of Matriarchal Prehistory combines a serious scrutiny of popular, as well as more academic writing on the presumed existence of a cult of the Goddess in ancient gynocentric societies. Even if after reading the monograph, you do not agree with the author’s ideological position, you will certainly have widened, in the process, your scope of this particular field of study and of the literature relevant to its analysis.